IS LIVING WITH A FATAL DISEASE WORTH LIVING?AN ETHICAL DILEMMA IN DO-NOT-RESUSCITATE (DNR) DECISION-MAKING (Kashf Journal of Multidisciplinary Research, 2026)
Patients with poor prognosis are often considered for do-not-resuscitate (DNR) orders, raising complex ethical, clinical, and communication challenges. This paper explores how DNR decisions are made, implemented, and communicated within healthcare settings, particularly in oncology care. The primary ethical responsibility of healthcare professionals is to maximize patient benefit while minimizing harm. However, conflicts frequently arise between patient autonomy, family wishes, and clinical judgment.This paper presents a case of a young patient with metastatic cancer where disagreement occurred between the healthcare team and family regarding DNR status. Ethical principles, including autonomy, beneficence, and non-maleficence, are critically analyzed alongside religious perspectives, particularly within the Islamic context. The discussion emphasizes that while patient autonomy is central, futile interventions such as cardiopulmonary resuscitation (CPR) may be ethically withheld when deemed non-beneficial by clinicians. The paper highlights the need for structured policies, improved communication, and culturally sensitive approaches to DNR decision-making.